Dampak Sertifikasi Guru terhadap Peningkatan Kualitas Pembelajaran Peserta Didik - Siswandari --; Susilaningsih -- (Jurnal Pendidikan dan Kebudayaan, 2013)
The purpose of this study is to examine the impact of teacher certification to improve the quality of teaching-learning process. In detail the objectives are described as follows: 1) assess the condition of teachers’ academic who have been certified, especially in the implementation of their pedagogical and professional competencies in the learning process, 2) attempts of teachers to maintain their certification in improve pedagogical and professional competencies, and 3) the impact of teacher certification to improving the quality of learning process in the classroom. The study that took place in Surakarta using mixed method approachby developing result of qualitative research to design the quantitative approach. Simple random sampling was used for quantitative approach while Criterion-based selection was used to draw sample for qualitative approach. Informants and samples involved in this study were 96 certified teachers, 74 teachers who have not been certified and 17 principals, and 424 students. Data collection method used in this study was in-depth interview, observation, documentation and questionnaires. Both interactive method and descriptive statistic were applied to analyze the data. The results of study show: 1) only 37% of certified teachers who deliver material clearly, the ability to use learning media and technology, the ability to follow the development of science and technology and learning innovation, also ability to do continuous professional development, need to be improved; 2) to maintain their professionalism, discussions between peer who teach same subjects is the most desirable method applied; 3) certified teachers have not shown an increase in the quality of teaching- learning process in the classroom significantly. This is partly indicated by the teacher ability to explain the material is still low, there is still a lack of ability to apply learning technologies (about 25% stated less to enough) and 20% of teachers indicated less attention to their student individually. The results of this study are expected to contribute to local governments in developing sustainable professionalism (continuing professional development) for teachers of post certification and to the central government in developing policies related to the welfare of teachers in Indonesia.